Analisis SWOT pengadaan bahan baku pakan konsentrat sapi perah di Koperasi SAE Pujon Kabupaten Malang - Anie Eka Kusumastuti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The research was carried out at “SAE” Cooperative, Pujon, Malang District. The purposes of this study were (1) to analyze the internal and external condition of SAE Cooperative, (2) to determine the appropriate strategy of feed procurement in SAE Cooperatives based on present condition. SAE Cooperatives was selected to represent the developed dairy category in Malang District. Descriptive quantitative and SWOT analysis were carefully applied to the available data. The results showed that the condition of SAE Cooperative was better to develop concentrate feed production business. It has known from the Strengths (S) and Opportunities (O) factors score has implied good prospect (SO=4,93). Remarks can be drawn from the research that the suitable feed procurement strategy adopted by SAE Cooperative would Growth Strategy with rapid growth. It is recommended to SAE Cooperative should analyze the internal and external condition in order to anticipate the changes and the competition in the future. Keywords: SWOT analysis, feed procurement, concentrate dairy cattle